Methyl/alkyl‐coenzyme M reductase‐based anaerobic alkane oxidation in archaea. (18th May 2020) - Wang, Yinzhao; Wegener, Gunter; Ruff, S. Emil; Wang, Fengping
Summary: Methyl‐coenzyme M reductase (MCR) has been originally identified to catalyse the final step of the methanogenesis pathway. About 20 years ago an aerobic me thane‐oxidizing archaea (ANME) were discovered that use MCR enzymes to activate methane. ANME thrive at the thermodynamic limit of life, are slow‐growing, and in most cases form syntrophic consortia with sulfate‐reducing bacteria. Recently, archaea that have the ability to anaerobically oxidize non‐methane multi‐carbon alkanes such as ethane and n ‐butane were described in both enrichment cultures and environmental samples. These an aerobic multi‐carbon al ka ne‐oxidizing archaea (ANKA) use enzymes homologous to MCR named alkyl‐coenzyme M reductase (ACR). Here we review the recent progresses on the diversity, distribution and functioning of both ANME and ANKA by presenting a detailed MCR/ACR‐based phylogeny, compare their metabolic pathways and discuss the gaps in our knowledge of physiology of these organisms. To improve our understanding of alkane oxidation in archaea, we identified three directions for future research: (i) expanding cultivation attempts to validate omics‐based metabolic models of yet‐uncultured organisms, (ii) performing biochemical and structural analyses of key enzymes to understand thermodynamic and steric constraints and (iii) investigating the evolution of anaerobic alkane metabolisms and their impact on biogeochemical cycles.